Chasing shadows : a special agent's lifelong hunt to bring a Cold War assassin to justice - Burton, Fred (Palgrave Macmillan, 2011)
"In July 1973, a gunman stepped from behind a tree and fired five shots, point blank, into Josef Alon, a kind, unassuming Israeli Air Force pilot. Sixteen-year-old Fred Burton was deeply shocked by this crime that rocked his sleepy suburban neighborhood of Bethesda, Maryland. As it turned out, Alon wasn't just a pilot and family man--he was a high-ranking Israeli military official with intelligence ties. The assassin was never found and the case was closed. Then, in 2007, now State Department counterterrorism special agent Fred Burton reopened the case and successfully pursued the killer, bringing closure to a traumatized family. From swirling dogfights over Egypt and Hanoi to gun battles on the streets of Beirut, this action-packed history spans the globe and several fraught decades in our history. In its portrait of how power is used, misused, and sold to the most convenient bidder, Chasing shadows spins a gripping tale of agents, double agents, terrorists, and heroes as Burton chases leads around the globe in an effort to solve this decades-old murder"--Provided by publisher.